Pain and function in patients with chronic low back pain and leg pain after Zhineng Qigong – a quasi-experimental feasibility study - Gabriella Pozarek; Björn Strömqvist; Eva Ekvall Hansson; Gerd Ahlström (BMC Musculoskeletal Disorders, 2023)
Abstract Background Qigong includes training for body and mind, one method is Zhineng Qigong. Scientific literature on qigong for chronic low back pain (LBP) is sparse. This study aimed to investigate feasibility including evaluation of a Zhineng Qigong intervention for pain and other lumbar spine-related symptoms, disability, and health-related quality of life in patients with chronic LBP and/or leg pain. Methods Prospective interventional feasibility study without control group. Fifty-two chronic pain patients (18–75 years) with LBP and/or leg pain (Visual Analogue Scale ≥ 30) were recruited from orthopaedic clinics (spinal stenosis, spondylolisthesis, or segmental pain) and primary healthcare (chronic LBP). Patients from orthopaedic clinics were 1–6 years postoperative after lumbar spine surgery or on lumbar surgery waiting list. Patients received a 12-week training intervention with European Zhineng Qigong. The intervention consisted of face-to-face group activities in non-healthcare setting (4 weekends and 2 evenings per week), and individual Zhineng Qigong training. Main health outcomes were self-reported in a 14-day pain diary, Oswestry Disability Index (ODI), Short Form 36 version 2 (SF-36v2), and EuroQol 5 Dimensions 5 Levels (EQ-5D-5L), once directly before and once directly after the intervention. Results Recruitment rate was 11% and retention rate was 58%. Dropouts did not report higher pain (baseline), only 3 dropped out because of lumbar spine-related pain. Adherence was median 78 h group attendance (maximum 94 h) and 14 min daily individual training. Ability to collect outcomes was 100%. Thirty patients completed (mean 15 years symptom duration). Twenty-five had degenerative lumbar disorder, and 17 history of lumbar surgery. Results showed statistically significant (within-group) improvements in pain, ODI, all SF-36v2 scales, and EQ-5D-5L. Conclusions Despite low recruitment rate, recruitment was sufficient. A multicentre randomized controlled trial is proposed, with efforts to increase recruitment and retention rate. After this Zhineng Qigong intervention patients with chronic LBP and/or leg pain, also patients with considerable remaining LBP/sciatica after lumbar surgery, had significantly improved in pain and function. Results support involvement of postoperative patients in a future study. The results are promising, and this intervention needs to be further evaluated to provide the most reliable evidence. Trial registration NCT04520334. Retrospectively registered 20/08/2020.